Possible Benefits of a Low Protein Diet in Older Patients With CKD at Risk of Malnutrition: A Pilot Randomized Controlled Trial - Lara Caldiroli; Simone Vettoretti; Silvia Armelloni; Deborah Mattinzoli; Masami Ikehata; Paolo Molinari; Carlo Alfieri; Carlo Alfieri; Piergiorgio Messa; Piergiorgio Messa; Giuseppe Castellano; Giuseppe Castellano (Frontiers in Nutrition, 2022)
BackgroundCurrent guidelines do not clarify whether older patients with advanced chronic kidney disease (CKD) may benefit of low protein (LP) diet if they are at risk of malnutrition. We compared the effects of normocalorie/normoprotein (NP) and normocalorie/LP diet on nutritional status and metabolic complications related to the progression of kidney damage in these patients.MethodsThis pilot study had an open-label randomized-controlled design (ClinicalTrials.gov Id: NCT05015647). Thirty-five patients were treated for 6 months with two different diets (LP = 17) and (NP = 18). Malnutrition was assessed by the Malnutrition Inflammation Score and International Society of Renal Nutrition and Metabolism criteria. Renal function was assessed by creatinine and cystatin-C-based estimated glomerular filtration rate (eGFR).ResultsAt the end of the study, Malnutrition Inflammation Score was improved in both LP and NP groups (respectively: 3 ± 3 vs. 6 ± 1.5, p = 0.020 and 3 ± 2.5 vs. 6 ± 2, p = 0.012), prevalence of protein energy wasting syndrome decreased only in LP. LP group had higher eGFRcys-C (17 ± 6 vs. 12 ± 4 ml/min/1.73 m2; p < 0.05), lower serum urea (105 ± 65 vs. 138 ± 30 mg/dl; p < 0.05) and lower parathormone (68 ± 10 vs. 99 ± 61 ng/L; p < 0.05) than NP. Serum and urinary phosphorous did not change while fibroblast growth factor 23 (FGF23)-intact and FGF23 c-terminal increased in both groups [FGF23-intact in LP: 70 (48; 98) vs. 126 (90; 410) pg/ml, p < 0.01 and in NP: 86 (57; 194) vs. 143 (119; 186) pg/ml, p < 0.01; FGF23 c-terminal in LP: 77 (30.3; 112) vs. 111 (63; 384) RU/ml, p < 0.01 and in NP: 142 (56.6; 175) vs. 157 (76.7; 281) RU/ml, p < 0.01].ConclusionsLP diet has a favorable impact on nutritional status as much as NP diet with possible greater benefits on the progression of kidney disease and some of its metabolic complications.Clinical Trial Registrationhttps://clinicaltrials.gov/ct2/show/NCT05015647, identifier: NCT05015647.